Local Global Watchdogs: Trade, Sourcing and the Internationalization of Social Activism - Pamina Koenig; Sebastian Krautheim; Claudius Löhnert; Thierry Verdier (Center for Economic Studies and Ifo Institute (CESifo), 2021)
NGO campaigns against firms with value chains involving production in developing and emerging economies are a salient feature of economic globalization. What determines the patterns of the internationalization of NGO campaigns? Stylized facts obtained from recently available data containing 102 532 campaigns by 4 343 NGOs targeting 11 429 firms from 145 countries guide our theoretical analysis. We propose a model of global sourcing and international trade in which heterogeneous NGOs campaign against heterogeneous firms in response to infringements along their international value chains. We find that campaigns are determined by a triadic gravity equation, i.e. bilateral trade costs between the country of the NGO, the country of the firm and the sourcing country affect campaigns. Most notably, the latter implies that by advancing the internationalization of production, falling trade costs boost the internationalization of NGO campaigns. We use our data to estimate the NGO level triadic gravity equation implied by our model and find strong support for our predictions.
Keywords: F12; F14; F60; L31; O35; 330; international trade; international sourcing; gravity; NGOs; campaigns; social activism